The path dependence of district manager decision-space in Ghana - Kwamie, A.; Van Dijk, H.; Ansah, E.K.; Agyepong, I.A. (Oxford University Press, 2016)
The district health system in Ghana today is characterized by high resource-uncertainty and narrow decision-space. This article builds a theory-driven historical case study to describe the influence of path-dependent administrative, fiscal and political decentralization processes on development of the district health system and district manager decision-space. Methods included a non-exhaustive literature review of democratic governance in Ghana, and key informant interviews with high-level health system officials integral to the development of the district health system. Through our analysis we identified four periods of district health system progression: (1) development of the district health system (1970-85); (2) Strengthening District Health Systems Initiative (1986-93); (3) health sector reform planning and creation of the Ghana Health Service (1994-96) and (4) health sector reform implementation (1997-2007). It was observed that district manager decision-space steadily widened during periods (1) and (2), due to increases in managerial profile, and concerted efforts at managerial capacity strengthening. Periods (3) and (4) saw initial augmentation of district health system financing, further widening managerial decision-space. However, the latter half of period 4 witnessed district manager decision-space contraction. Formalization of Ghana Health Service structures influenced by self-reinforcing tendencies towards centralized decision-making, national and donor shifts in health sector financing, and changes in key policy actors all worked to the detriment of the district health system, reversing early gains from bottom-up development of the district health system. Policy feedback mechanisms have been influenced by historical and contemporary sequencing of local government and health sector decentralization. An initial act of administrative decentralization, followed by incomplete political and fiscal decentralization has ensured that the balance of power has remained at national level, with strong vertical accountabilities and dependence of the district on national level. This study demonstrates that the rhetoric of decentralization does not always mirror actual implementation, nor always result in empowered local actors. © The Author 2015.
Keywords: Complexity; Decentralization; Decision-space; District health systems; Ghana; Path dependence